Pengaruh Mutasi terhadap Kinerja Karyawan Melalui Kepuasan Kerja Karyawan: (Studi di PT Pegadaian Kanwil XII Surabaya) - Akbar Wicaksono; Chamariyah Chamariyah; Indra Prasetyo (Universitas 45 Surabaya, 2025)
Akbar Wicaksono, 2025. The Influence of Mutation on Employee Performance Through Employee Job Satisfaction (Study at PT Pegadaian Regional Office XII Surabaya) Postgraduate Program, Wijaya Putra University, Surabaya. This study is explanatory in nature, utilizing a quantitative approach. The sample consisted of 65 participants. The analysis tool used was Smart PLS (Partial Least Squares). The objectives of this study are: 1) To test and analyze the direct effect of mutation on employee performance at PT Pegadaian Regional Office XII Surabaya. 2) To test and analyze the direct effect of mutation on employee job satisfaction at PT Pegadaian Regional Office XII Surabaya. 3) To test and analyze the direct effect of job satisfaction on employee performance at PT Pegadaian Regional Office XII Surabaya. 4) To test and analyze the indirect effect of mutation on employee performance at PT Pegadaian Regional Office XII Surabaya through job satisfaction. The results of the study show that: 1) Mutation has a significant effect on employee performance. 2) Mutation has a significant effect on employee job satisfaction. 3) Job satisfaction has a significant effect on employee performance. 4) Mutation has a significant effect on employee performance through job satisfaction. This study provides valuable insights into how the employee mutation process can enhance performance through job satisfaction, which can serve as a basis for decision-making by the company's management.